Recent developments in the design of rapid response cells for laser ablation-inductively coupled plasma-mass spectrometry and their impact on bioimaging applications. Issue 2 (10th December 2015) - Van Malderen, Stijn J. M.; Managh, Amy J.; Sharp, Barry L.; Vanhaecke, Frank
Abstract : This review covers developments in the design of Laser Ablation (LA) cells, the associated transport tubing assembly, and their coupling to Inductively Coupled Plasma-Mass Spectrometry (ICP-MS) instrumentation. Abstract : This review covers developments in the design of Laser Ablation (LA) cells, the associated transport tubing assembly, and their coupling to Inductively Coupled Plasma-Mass Spectrometry (ICP-MS) instrumentation. Recent ablation cell designs have reduced the pulse response duration for a single laser shot to <10 ms, using the criterion of the full peak width at 1% of the height of the maximum signal intensity. The evolution towards these low dispersion systems has been profoundly influenced by our understanding of processes driving the initial dispersion, of the design aspects of the cell and tubing that influence transport-induced dispersion and transport efficiency, and of limitations imposed by the temporal resolution of ICP-MS instruments, all of which are discussed. Rapid response LA-ICP-MS systems greatly benefit throughput and sensitivity, which are key parameters in 2D and 3D imaging at high lateral resolution. The analysis and imaging of biological material has come to the forefront as a key application of LA-ICP-MS. The impact of the technical developments in LA-ICP-MS systems on emerging applications, including multiplexed metal-tagged antibody detection (for immunohistochemistry), nanoparticle and compound hypo- and hyperaccumulation, and (intra-) cellular/histological studies, is also discussed.